2012
DOI: 10.2527/jas.2011-4228
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism association study for backfat and intramuscular fat content in the region between SW2098 and SW1881 on pig chromosome 61

Abstract: This study was carried out to identify SNP associated with fatness traits on pig chromosome 6. In total, 11,067 putative genomic variations were detected in 125 complete bacterial artificial chromosome sequences corresponding to the region between SW2098 and SW1881, which harbors multiple QTL affecting intramuscular fat content (IMF) and backfat thickness (BFT). Among 173 putative SNP validated by MassArray, 120 SNP were used in an association study on 541 offspring produced by a cross of Korean native pig and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In the present study, the c.919G>A, 307G>R CBG variant was significantly associated with backfat thickness, postmortem pH 24h , CIE a*, CIE b*, water-holding capacity, fat content, moisture content, protein content, cooking loss, and shear force (Table 2). Its association with drip loss has been also reported previously (Esteve et al 2011; Lee et al (2012), who reported that backfat thickness and fat content are associated with lean-meat content. Furthermore, in the present study, the variant G allele was associated with decreases in backfat thickness, post-mortem pH 24h , CIE a*, fat content, and cooking loss, but with increases in CIE b*, water-holding capacity, moisture content, protein content, and shear force.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, the c.919G>A, 307G>R CBG variant was significantly associated with backfat thickness, postmortem pH 24h , CIE a*, CIE b*, water-holding capacity, fat content, moisture content, protein content, cooking loss, and shear force (Table 2). Its association with drip loss has been also reported previously (Esteve et al 2011; Lee et al (2012), who reported that backfat thickness and fat content are associated with lean-meat content. Furthermore, in the present study, the variant G allele was associated with decreases in backfat thickness, post-mortem pH 24h , CIE a*, fat content, and cooking loss, but with increases in CIE b*, water-holding capacity, moisture content, protein content, and shear force.…”
Section: Discussionsupporting
confidence: 76%
“…Of the four polymorphic sites, g.955T>C SNP was previously found (kps6413; Lee et al, 2012), and the other SNPs were newly identified in this study (g.196A>G; ss974514574, g.392C>A; ss974514575, g.3247A>T; ss974514576). To estimate the genotypic and allelic frequencies for the four SNPs, 678 Berkshire pigs were genotyped and the results are given in Table 2.…”
Section: Snp Identification and Association Studysupporting
confidence: 57%
“…It was also associated with drip loss, MC_L, and moisture traits (P < 0.05). GADD45A was previously reported to be significantly associated with IMF and BF traits in a reference family crossed by Korean native pig and Landrace (Lee et al, 2012). Despite the different pig populations, this SNP had the same effect on IMF and BF traits.…”
Section: Snp Identification and Association Studymentioning
confidence: 86%
See 2 more Smart Citations